Fatwa DSN MUI In Managing The Dispute Settlement Of Sharia Economic In Indonesia Through Basyarnas - Nunung Radliyah; Dewi Nurul Musjtari; Ro'fah Setyowati (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
Sharia Council is an institution that plays a role in securing the standard of Sharia in every Islamic Financial institution in the world. In Indonesia, the role is conducted by the National Sharia Council (DSN) established by the Indonesian Ulema Council (MUI) in 1998, strengthened by the Decree of the MUI Leadership Board. Kep-754/MUI/II/1999 dated February 10, 1999. The existence of MUI DSN in managing the settlement of sharia banking disputes has not been fully recognized by the people of Indonesia. It can be seen in the implementation of sharia contracting in sharia banking has not yet decided dispute resolution option through National Syariah Arbitration Board (BASYARNAS). The purpose of writing a paper is to know the legal basis of the binding force of the Fatwa DSN in arranging the settlement of dispute Sharia Economy in Indonesia through BASYARNAS and its consequences for the Islamic financial institutions (LKS) who disobey the fatwa DSN. This research is a normative research with the philosophical, juridical and sociological approach. Data analysis with qualitative descriptive. The results of this study indicate that the legal basis of the power of the DSN Fatwa in regulating the settlement of Sharia Banking disputes is Article 26 of Law No. 21 Th. 2008 and Article 31 of Decree of the Board of Managing Directors of Bank Indonesia Number 32/34/1999. There will a negative impact for LKS do not comply with the content of the DSN Fatwa, such as the difficulty in carry out its activities, aside of negatively influencing the performance and level of credibility of DPS in LKS.